1997
DOI: 10.1021/jp971229c
|View full text |Cite
|
Sign up to set email alerts
|

What Controls Partitioning of the Nucleic Acid Bases between Chloroform and Water?

Abstract: The free energies of solvation for six nucleic acid bases in water and chloroform are predicted using the SM5.4/A quantum mechanical self-consistent-field solvation model. We obtain a mean unsigned deviation from experiment of 0.2 log 10 units in the partition coefficients, lending extra credibility to the predicted solvation free energies. Predictions are then made for an additional six unnatural nucleic acid bases for which no experimental data are available. Functional group contributions to the solvent-sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 43 publications
2
36
0
Order By: Relevance
“…The contributions to the free energy of transfer from water to olive oil by F, and Cl in enflurane are −0.49 kcal/mol and −1.16 kcal/mol respectively, and in halothane the contributions of F and Br are −0.48 kcal/mol and −1.13 kcal/mol, respectively. These results agree with prior observations106 that group free energies of transfer are highly transferable for substituted nucleic acids partitioning between water and chloroform. The difference in the effect of F upon the transfer free energy compared to the effect of chlorine is quite large, ~0.7 kcal/mol, while the difference between the energetically more favorable Cl and Br is very small.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The contributions to the free energy of transfer from water to olive oil by F, and Cl in enflurane are −0.49 kcal/mol and −1.16 kcal/mol respectively, and in halothane the contributions of F and Br are −0.48 kcal/mol and −1.13 kcal/mol, respectively. These results agree with prior observations106 that group free energies of transfer are highly transferable for substituted nucleic acids partitioning between water and chloroform. The difference in the effect of F upon the transfer free energy compared to the effect of chlorine is quite large, ~0.7 kcal/mol, while the difference between the energetically more favorable Cl and Br is very small.…”
Section: Resultssupporting
confidence: 92%
“…(Tables 11 and 12). The method for partitioning SM x solvation free energies into group contributions has been explained elsewhere 106. One salient example in the current data set is the positive contribution fluorine atoms make to the total free energy of solvation of fluorinated compounds in olive oil (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The H bonding properties of ClU and T are probably not substantially different, because the 5-Cl and 5-CH 3 substituents have a similar hydrophobic effect (π, Table 2), and previous studies have shown that the hydrophobicity of uracil was increased to the same extent by halogen (5-Br) and methyl (5-CH 3 ) substituents. 65,66 Moreover, the enthalpy of base pairing for the isolated A·T and A·ClU pairs was calculated to be 12.1 and 12.8 kcal/mol at the MP2(full)/6-311+G(2d,2p)//B3LYP/6-31G* level of theory. 43,67 Thus, the 572-fold greater activity of hTDG against ClU over T can be most readily explained by the superior leaving ability of ClU compared to T (ΔpK a N1 = −2.05), and is consistent with the higher intrinsic reactivity (k non ) of CldU over dT (Table 1).…”
Section: Htdg Activity Against 5-substituted Uracilsmentioning
confidence: 99%
“…The optimized dielectric constant was used for the computation of electrostatics at the SM5. A point that merits emphasis is that application of the SMx models to predict solvation or partitioning behavior can certainly be useful as a predictive exercise, but a potentially still more important feature of the models is that the free energy associated with the particular phase transfer can be decomposed into atomic or group contributions, and thus interpreted in a fragment basis [163,164] For instance, Figure 3 illustrates the correlation between experimental and predicted logK OC values for polychlorinated biphenyls (PCBs). There is a systematic error of about 1 log unit in the absolute accuracy of the predictions, but otherwise a fairly good correlation (R 2 = 0.86).…”
Section: Smx Models For Other Condensed Phasesmentioning
confidence: 99%